Selenium‐Doped Carbon Quantum Dots Act as Broad‐Spectrum Antioxidants for Acute Kidney Injury Management - Rosenkrans, Zachary T.; Sun, Tuanwei; Jiang, Dawei; Chen, Weiyu; Barnhart, Todd E.; Zhang, Ziyi; Ferreira, Carolina A.; Wang, Xudong; Engle, Jonathan W.; Huang, Peng; Cai, Weibo (Advanced science, 2020)
The manifestation of acute kidney injury (AKI) is associated with poor patient outcomes, with treatment options limited to hydration or renal replacement therapies. The onset of AKI is often associated with a surfeit of reactive oxygen species. Here, it is shown that selenium‐doped carbon quantum dots (SeCQDs) have broad‐spectrum antioxidant properties and prominent renal accumulation in both healthy and AKI mice. Due to these properties, SeCQDs treat or prevent two clinically relevant cases of AKI induced in murine models by either rhabdomyolysis or cisplatin using only 1 or 50 µg per mouse, respectively. The attenuation of AKI in both models is confirmed by blood serum measurements, kidney tissue staining, and relevant biomarkers. The therapeutic efficacy of SeCQDs exceeds amifostine, a drug approved by the Food and Drug Administration that also acts by scavenging free radicals. The findings indicate that SeCQDs show great potential as a treatment option for AKI and possibly other ROS‐related diseases. The specific renal accumulation and excellent antioxidant properties of SeCQDs allows prevention and treatment of acute kidney injury.